EVALUATION OF BASIC LITERACY EDUCATOR AS SOCIAL CHANGE AGENT - Wulandari, Apriyanti (Universitas Pendidikan Indonesia, 2018)
Literacy is not limited to the ability to read, write, and arithmetic, but also the application of that ability to enhance the quality of life. The purpose of this study is to evaluate the role of literacy educators as agents of social change. This research is based on evaluation model with Change Model approach. The population of this study are the educators in the two institutes of basic literacy education program in Cirebon Regency. The results of this study showed that basic literacy educators have not received appropriate compensation so that their paradigm as an agent of social change has not yet been arised. Researchers recommend to reorganize the training system that has been implemented so that they get recognition from the government.